Normal and pathological neuronal distribution of the human mesencephalic locomotor region. Issue 2 (28th November 2018) - Sébille, Sophie B.; Rolland, Anne‐Sophie; Faillot, Matthieu; Perez‐Garcia, Fernando; Colomb‐Clerc, Antoine; Lau, Brian; Dumas, Sylvie; Vidal, Sara Fernandez; Welter, Marie‐Laure; Francois, Chantal; Bardinet, Eric; Karachi, Carine
ABSTRACT: Background: Deep brain stimulation of the pedunculopontine nucleus has been performed to treat dopamine‐resistant gait and balance disorders in patients with degenerative diseases. The outcomes, however, are variable, which may be the result of the lack of a well‐defined anatomical target. Objectives: The objectives of this study were to identify the main neuronal populations of the pedunculopontine and the cuneiform nuclei that compose the human mesencephalic locomotor region and to compare their 3‐dimensional distribution with those found in patients with Parkinson's disease and progressive supranuclear palsy. Methods: We used high‐field MRI, immunohistochemistry, and in situ hybridization to characterize the distribution of the different cell types, and we developed software to merge all data within a common 3‐dimensional space. Results: We found that cholinergic, GABAergic, and glutamatergic neurons comprised the main cell types of the mesencephalic locomotor region, with the peak densities of cholinergic and GABAergic neurons similarly located within the rostral pedunculopontine nucleus. Cholinergic and noncholinergic neuronal losses were homogeneous in the mesencephalic locomotor region of patients, with the peak density of remaining neurons at the same location as in controls. The degree of denervation of the pedunculopontine nucleus was highest in patients with progressive supranuclear palsy, followed by Parkinson's disease patients with falls. Conclusions: The peak density of cholinergic and GABAergic neurons was located similarly within the rostral pedunculopontine nucleus not only in controls but also in pathological cases. The neuronal loss was homogeneously distributed and highest in the pedunculopontine nucleus of patients with falls, which suggests a potential pathophysiological link. © 2018 International Parkinson and Movement Disorder Society